Flanking sound transmission in wood-framed construction - Nightingale, T.R.T.; Halliwell, R.E.; Quirt, J.D. (Canadian Acoustics, 2001)
An overview is given on selected results from a research project to study sound and fire resistance of wall/floor junctions intended for multi-family residential buildings. It is emphasized that lower apparent TL observed in the field is often due to flanking.